Can extra care housing support the changing needs of older people living with dementia?. (July 2020) - Evans, Simon Chester; Atkinson, Teresa; Cameron, Ailsa; Johnson, Eleanor K; Smith, Randall; Darton, Robin; Porteus, Jeremy; Lloyd, Liz
With over two-thirds of people with dementia living in the community and one-third of those living alone, it is important to consider the future housing needs of this population, particularly as symptoms of cognitive impairment increase. Policy in England has focused on enabling people living with dementia to remain in their own homes for as long as possible, often with the support of a family carer. However, many people struggle to maintain an acceptable quality of life in their own homes as their dementia advances, often due to the design limitations of mainstream housing and the challenge of finding specialist domiciliary care that is affordable and of sufficient quality. Extra care housing offers a model that aims to support older people living in their own apartments, whilst also offering specialist person-centred care as and when it is needed. This paper reports on a longitudinal project that explored how extra care housing can respond to the changing social care needs of residents, including those living with dementia. Participants included residents and staff from four extra care housing schemes, one of which was a specialist dementia scheme, in two regions of England. Interviews were carried with 51 residents across 4 rounds at 5 month intervals between October 2015 and June 2017. Interviews were also carried out with 7 managers, 20 care staff and 2 local authority commissioners of housing for older people. Key factors included person-centred care and support, flexible commissioning and staffing, appropriate design of the environment and suitable location of the scheme within the wider community. The challenge of delivering services that addresses these issues during a period of reduced public spending is acknowledged. Further research is suggested to compare different approaches to supporting people with dementia, including integrated and separated accommodation, and different stages of dementia.